Artificial Intelligence in Journalism — Opportunities, Bias, and Ethical Dilemmas - Uzma Abbas (Journal of Advanced Research in Journalism & Mass Communication, 2025)
Artificial intelligence (AI) is reshaping journalism through automated content creation, data-driven analytics, and personalized news delivery. According to recent studies, over 50% of major global news agencies now employ AI-assisted tools for tasks ranging from automated reporting to real-time audience analytics. While AI promises efficiency and precision, it also introduces risks of bias, misinformation, and loss of human editorial judgment. This paper examines the dual nature of AI in journalism—its transformative opportunities and the ethical dilemmas it creates. It explores AI’s role in news automation, verification, audience targeting, and fact-checking, along with emerging challenges of transparency, algorithmic fairness, and accountability. The study concludes that integrating AI responsibly into journalism requires strong ethical guidelines, interdisciplinary collaboration, and public awareness to ensure technology serves truth rather than distorting it. The paper further suggests developing unified ethical auditing systems for AI-powered newsrooms to maintain accountability and public trust.